School Development Through Teacher Research : Lesson and Learning Studies in Sweden and Tanzania - Eriksson, Inger; Eriksson, Inger; O-Saki, Kalafunja Mlang'a; O-Saki, Kalafunja Mlang'a (Book collections on Project MUSE., 2018)
School Development through Teacher Research -- Lesson and Learning Studies in Sweden and Tanzania presents the results from a three-year-long joint research project conducted by educational researchers from Tanzania and Sweden. Even though the country contexts differ in social, economic as well as educational conditions, including teacher education and classroom standards, many recurrent education challenges are shared. These include the tendency to make educational reforms with little or no input from professionals. The new educational reforms in both countries put a much higher responsibility on teachers; teachers must be able to organise teaching that enables all students to develop required abilities/competencies. Thus, teachers need tools to develop knowledge that can contribute to their professional knowledge base. With an overall interest in issues of teaching and action research, this joint project aimed to use Lesson and Learning Study as models for developing and improving the quality of teaching and learning in schools. The research project was realised through four case studies in each country with a focus on students' development of specific capabilities and values Science, Vocational Skills/Home and Consumer Studies, English as second language and Mathematics in grades 6-7. Complementing the cases School Development through Teacher Research-Lesson and Learning Studies in Sweden and Tanzania offers an introductory background to Lesson and Learning Studies as models for teacher-driven research and school development. The book is written to support teachers and teacher educators' wishing to reflect about learning and the struggle of learners to discern various concepts, principles and practices. As well as those who genuinely wish to see serious learning take place, rather than simply seeing content 'covered' -- including curriculum designers and developers, educational researchers, educational supervisors and leaders and student-teachers as well as students of pedagogy and didactics. We dedicate the book to teacher educators, teachers and school leaders who are seriously striving to enhance students' learning and understanding in different subject areas.